(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2025)
Acute obstructive bronchitis remains one of the most prevalent and severe respiratory diseases in children. Understanding the pathogenetic role of immune status and cytokines can provide deeper insight into the mechanisms underlying the development of AOB. This knowledge is essential for developing effective diagnostic and treatment strategies for frequently ill children. The primary focus of scientific research is to investigate the mechanisms of disease progression, identify the clinical features, and assess the impact of immune status and cytokines in acute obstructive bronchitis among frequently ill children. The goal is to develop pathogenetically based treatment methods and preventive measures. In our country, extensive efforts are being made to ensure early diagnosis and prevention of somatic diseases in children, with particular emphasis on bronchopulmonary pathology.